Experimental investigation of the rheological behaviors of polypropylene in a capillary flow. Issue 22 (24th February 2016) - Meng, Limin; Wu, Daming; Kelly, Adrian; Woodhead, Mike; Liu, Ying
ABSTRACT: The rheological characterization of polymer melts is strongly related to their material properties. In this study, we focused on the rheological behaviors of a polypropylene (PP) melt through a capillary die. With an advanced twin‐bore capillary rheometer with dies measuring 1.0, 0.5, and 0.25 mm in diameter, experiments were performed over a shear‐rate range of 3 × 10 2 to 5 × 10 3 s −1 at three temperatures, 210, 220, and 230 °C. The results demonstrate that the geometry dependence of the PP viscosity relied on the die diameter and the temperature of the PP melt. The viscosity values of the PP melt in the 0.25‐mm diameter die were higher than were those in the 0.5‐ and 1.0‐mm dies at 220 and 230 °C. However, the viscosity values in all of the tested dies were similar at 210 °C. The tendency for the viscosity to decrease as the temperature of the polymer melt increased weakened in the 0.25‐mm diameter die. As a result, the pressure applied to the PP melt in the 0.25‐mm diameter die increased; this caused a decrease in the free volume between molecules. On the basis of the Barus equation, the contribution of pressure to the changed viscosity in each die at each of the tested temperatures was calculated and was found to be as high as 32.86% in the 0.25‐mm die at 230 °C. Additionally, the effect of the wall slip on the geometry dependence of the PP viscosity in the tested dies was investigated with a modified Mooney method. The values of the slip velocity revealed that wall slip occurred only in the 0.25‐mm die at 210 °C. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43459. Abstract :